Randomized controlled trial of anti-smoking advice by nurses in general practice. - Sanders, D; Fowler, G; Mant, D; Fuller, A; Jones, L; Marzillier, J (1989)
Practice nurses are playing an increasingly prominent role in preventive care, including the provision of anti-smoking advice during routine health checks. A randomized controlled trial was designed to assess the effectiveness of anti-smoking advice provided by nurses in helping smokers to stop smoking. A total of 14,830 patients aged 16-65 years from 11 general practices completed a brief questionnaire on general health, including smoking status, at surgery attendance. The doctor identified 4330 smokers and randomly allocated 4210 to control or intervention groups. The doctor asked those in the intervention group to make an appointment with the practice nurse for a health check. The attendance rate at the health check was 26%. Smokers were sent follow-up questionnaires at one month and one year, and those who did not respond to two reminders were assumed to have continued to smoke. There was no significant difference in reported cessation between the intervention and control groups at one month or one year. However, there was a significant difference in the proportion of patients who reported giving up within one month and who had not lapsed by one year--0.9% in controls and 3.6% in the intervention group (P less than 0.01). Nevertheless, the effect of the nurse intervention itself may be small as the sustained cessation rate in attenders was only 42.4% higher than in non-attenders. The deception rate in reporting cessation, as measured by urinary cotinine, was of the order of 25%.